The molecular and cellular basis for oncogene collaboration in acute myeloid leukaemia - Di Genua, C (2018)
Acute myeloid leukaemia (AML) is an aggressive malignancy of the bone marrow caused by the uncontrollable proliferation of immature myeloid cells that fail to terminally differentiate. Mutations in AML are acquired hierarchically, where pre-leukaemic mutations are acquired within haematopoietic stem cells (HSCs); while secondary mutations, such as signalling mutations, are acquired within downstream pre-leukaemic progenitor cells. Why certain mutations are pre-leukaemic and thus acquired within the HSCs, compared to others, and the mechanism by which pre-leukaemic and secondary mutations collaborate, are still poorly understood. Utilising knock-in mutant mouse models we showed that HSCs expressing the pre-leukaemic fusion protein Aml1-ETO conferred a competitive advantage. However, activated K-Ras in Aml1-ETO-expressing HSCs had a marked detrimental effect, leading to cell cycle activation and loss of self-renewal associated gene expression. This provides a mechanism for the observed absence of a signalling mutation in pre-malignant HSCs. The specific association between the biallelic CEBPA and zinc finger 1 (ZF1) GATA2 mutations is observed in AML as well as acute erythroid leukaemia (AEL). We show the mutations collaborate to generate a model of AEL with bi-lineage transformation of the myeloid and erythroid lineages. This is due to the biallelic Cebpa mutations reprogramming the neutrophil-monocyte progenitors (NMPs) to acquire ectopic erythroid potential, while the Gata2 mutation synergises with the Cebpa mutations to impair erythroid differentiation progression. The investigation of ZF1 Gata2 mutation in isolation at both heterozygous and homozygous level showed the ZF1 mutation results in loss of Gata2 function only when the mutation is homozygous. As ZF1 GATA2 mutations are heterozygous in patients, this data supports the findings that ZF1 GATA2 and CEBPA mutations must work synergistically to cause leukaemia development.